Ethylene-based ionomer for gaskets and molded body thereof
Patent Information
- Application Number
- JP2020112675
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-01
- Filing Date
- 2020-06-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-06-30
AI Technical Summary
【0020】 本発明により、簡便な方法で作製可能であり、柔軟性、弾性回復性、耐衝撃性及び耐摩耗性のバランスに優れるガスケット用エチレン系アイオノマー並びにその成形体を提供することが可能となる。
Smart Images

Figure 0007642987000017 
Figure 0007642987000018 
Figure 0007642987000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an ethylene-based ionomer for gaskets which can be produced by a simple method and has an excellent balance of flexibility, elastic recovery, impact resistance and abrasion resistance, and a molded article thereof. [Background technology]
[0002] Ethylene-based ionomers are resins that use ethylene-unsaturated carboxylic acid copolymers as the base resin and are intermolecularly bonded with metal ions such as sodium and zinc (Patent Document 1). They are characterized by their toughness, elasticity, flexibility, abrasion resistance, transparency, etc. Currently, commercially available ethylene-based ionomers include "Surlyn (registered trademark)", a sodium salt or zinc salt of ethylene-methacrylic acid copolymer developed by Dupont, and "Himilan (registered trademark)" sold by Dow Mitsui Polychemicals.
[0003] The ethylene-unsaturated carboxylic acid copolymers used as the base resins for these currently commercially available ethylene-based ionomers all use polar group-containing olefin copolymers obtained by polymerizing ethylene and polar group-containing monomers such as unsaturated carboxylic acids by high-pressure radical polymerization. The high-pressure radical polymerization method has the advantage that it can polymerize relatively any type of polar group-containing monomer at low cost. However, the molecular structure of the polar group-containing olefin copolymer produced by the high-pressure radical polymerization method has many irregular long-chain branches and short-chain branches, as shown in the image diagram in Figure 1, and has the disadvantage of being insufficient in terms of strength.
[0004] Conventionally, methods have been sought to produce polar group-containing olefin copolymers with a linear molecular structure, as shown in the image diagram in Figure 2, using a polymerization method that uses a catalyst. However, polar group-containing monomers are generally catalyst poisons, making polymerization difficult. In fact, it has been considered difficult for many years to obtain polar group-containing olefin copolymers with the desired physical properties using an industrially inexpensive and stable method.
[0005] However, in recent years, a method has been proposed for industrially producing polar group-containing olefin copolymers having a substantially linear molecular structure at low cost and in a stable manner by using a new catalyst and a new production method developed by the applicants of the present application. The applicants of the present application have reported that they have succeeded in producing a copolymer of ethylene and t-butyl acrylate using a late transition metal catalyst as a method for producing a polar group-containing olefin copolymer that serves as the base resin for an ethylene-based ionomer, and modifying the resulting polar group-containing olefin copolymer by heat or acid treatment to form an ethylene-acrylic acid copolymer, which is then reacted with metal ions to produce a binary ionomer (Patent Document 2).
[0006] On the other hand, in recent years, resin gaskets have been widely used as bottle cap closure liners and sealing parts for electronic devices due to their ease of production and shaping. Resin gaskets are characterized by having sufficient flexibility to increase adhesion and a certain level of elastic recovery to maintain the seal with the sealed part. Furthermore, resin gaskets used in sealing parts such as bottle cap closure liners and hinge parts of electromagnetic devices are required to have not only flexibility and elastic recovery, but also durability that can withstand wear caused by repeated rubbing from opening and closing bottles and operation of the hinge part, as well as tearing caused by large deformation.
[0007] Patent Document 3 discloses, as a material useful for producing a gasket, a polymer composition containing at least an ethylene / α-olefin copolymer and at least one other polymer, wherein the other polymer is a second ethylene / α-olefin copolymer, an elastomer, a polyolefin, a polar polymer, and an ethylene / carboxylic acid copolymer or an ionomer thereof. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] U.S. Pat. No. 3,264,272 [Patent Document 2] JP 2016-79408 A [Patent Document 3] Special Publication No. 2008-545017 Summary of the Invention [Problem to be solved by the invention]
[0009] The composition of Patent Document 3 has elastic recovery and abrasion resistance at a certain level or higher, but is still insufficient. In addition, the composition of Patent Document 3 requires homogeneous kneading of multiple materials to stabilize the quality, which requires the use of a molding machine with high kneading capacity or requires pre-processing such as compounding in a separate process, resulting in increased production costs, and thus has a problem of significant constraints on production.
[0010] In view of the above-mentioned state of the art, the present application aims to provide an ethylene-based ionomer for gaskets that can be produced by a simple method and has an excellent balance of flexibility, elastic recovery, impact resistance, and abrasion resistance, as well as a molded article thereof. [Means for solving the problem]
[0011] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems and found that, by using a specific ethylene-based ionomer, it is possible to produce, in a simple manner, an ethylene-based ionomer for gaskets having an excellent balance of flexibility, elastic recovery, impact resistance, and abrasion resistance. The ethylene-based ionomer described in Patent Document 2 is a novel ethylene-based ionomer that has not been seen before, in which the base resin has a substantially linear molecular structure and also functions as an ionomer. Its physical properties, etc. are significantly different from those of conventional ethylene-based ionomers, and its unique characteristics and suitable applications were unknown. Ethylene-based ionomers basically do not have high elastic recovery properties. However, the present inventors have discovered that a specific substantially linear ethylene-based ionomer has unexpectedly excellent elastic recovery properties, and that the ionomer has an excellent balance of flexibility, elastic recovery properties, impact resistance, and abrasion resistance, thereby completing the present invention. The gist of the present invention is as follows.
[0012] (1) An ethylene-based ionomer for gaskets satisfying the following (a) to (f): (a) A copolymer (P) containing, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, in which at least a portion of the carboxyl groups and / or dicarboxylic anhydride groups are converted into a metal-containing carboxylate containing at least one metal ion selected from Groups 1, 2, or 12 of the periodic table, and which has a complex modulus G measured with a rotational rheometer * The phase angle δ at the absolute value of 0.1 MPa is 50 to 75 degrees. (b) The melt flow rate (MFR) at a temperature of 190°C and a load of 2.16 kg is 0.1 to 30 g / 10 min. (c) The elastic recovery rate in a tensile test is 65 to 100%. (d) The tensile modulus is 20 to 350 MPa. (e) Tensile impact strength of 700KJ / m 2 That's all. (f) The amount of wear in an abrasion test is less than 10 mg.
[0013] (2) The copolymer (P) 13 The ethylene-based ionomer according to (1), having a number of methyl branches calculated by C-NMR of 50 or less per 1,000 carbons.
[0014] (3) The copolymer (P) 13 The ethylene-based ionomer according to (1), having a number of methyl branches per 1,000 carbons calculated by C-NMR of 5 or less.
[0015] (4) The ethylene-based ionomer according to any one of (1) to (3), wherein the structural unit amount of the structural unit (B) in the copolymer (P) is 2 to 20 mol %.
[0016] (5) The ethylene-based ionomer according to any one of (1) to (4), wherein the structural unit (A) is a structural unit derived from ethylene.
[0017] (6) The ethylene-based ionomer according to any one of (1) to (5), wherein the copolymer (P) is produced using a transition metal catalyst containing a transition metal of Groups 8 to 11 of the periodic table.
[0018] (7) The ethylene-based ionomer according to (6), wherein the transition metal catalyst is a metal complex containing a ligand selected from phosphorus sulfonic acid or phosphorus phenol and a transition metal selected from nickel or palladium.
[0019] (8) The ethylene-based ionomer for gaskets according to any one of (1) to (7), characterized in that the copolymer (P) is a copolymer further containing, as an essential constituent unit, a structural unit (C) which is a compound having one or more carbon-carbon double bonds in its molecular structure other than the structural unit (A) and the structural unit (B). (9) The ethylene-based ionomer for gaskets according to (8), characterized in that the structural unit (C) in the copolymer (P) is a non-cyclic monomer which is a (meth)acrylic acid ester or a cyclic monomer which is a norbornene-based olefin. (10) A gasket comprising the ethylene-based ionomer according to any one of (1) to (9). Effect of the Invention
[0020] According to the present invention, it is possible to provide an ethylene-based ionomer for gaskets that can be produced by a simple method and has an excellent balance of flexibility, elastic recovery, impact resistance and abrasion resistance, and a molded article thereof. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is an image of the molecular structure of a hyperbranched olefin copolymer polymerized by a high-pressure radical polymerization process. [Diagram 2] FIG. 2 is an image of the molecular structure of a linear olefin copolymer polymerized using a metal catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention provides an ethylene-based ionomer for gaskets that satisfies the following (a) to (f). (a) A copolymer (P) containing, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, in which at least a portion of the carboxyl groups and / or dicarboxylic anhydride groups are converted into a metal-containing carboxylate containing at least one metal ion selected from Groups 1, 2, or 12 of the periodic table, and which has a complex modulus G measured with a rotational rheometer * The phase angle δ at the absolute value of 0.1 MPa is 50 to 75 degrees. (b) The melt flow rate (MFR) at a temperature of 190°C and a load of 2.16 kg is 0.1 to 30 g / 10 min. (c) The elastic recovery rate in a tensile test is 65 to 100%. (d) The tensile modulus is 20 to 350 MPa. (e) Tensile impact strength of 700KJ / m 2 That's all. (f) The amount of wear in an abrasion test is less than 10 mg.
[0023] The ethylene-based ionomer and its uses according to the present invention will be described in detail below for each item. In this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid. In this specification, "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower and upper limits. In this specification, a copolymer means a binary or higher copolymer containing at least one type of unit (A) and at least one type of unit (B). In addition, in this specification, the ionomer refers to an ionomer of a binary or higher copolymer that contains the structural unit (A) and a structural unit (B') in which at least a portion of the structural unit (B) is converted to a metal-containing carboxylate, and may further contain the structural unit (B).
[0024] 1. Ethylene-based ionomers The ethylene-based ionomer according to the present invention is characterized in that it contains, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and uses as a base resin a copolymer (P) in which these are copolymerized, preferably randomly copolymerized, in a substantially linear manner, and at least a portion of the carboxyl groups and / or dicarboxylic anhydride groups of the structural unit (B) are converted to a metal-containing carboxylate containing at least one metal ion selected from Groups 1, 2, or 12 of the periodic table.
[0025] (1) Structural unit (A) The structural unit (A) is at least one structural unit selected from the group consisting of structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms. The α-olefins involved in the present invention have the structural formula: CH2=CHR 18 is an α-olefin having 3 to 20 carbon atoms (R 18 is a hydrocarbon group having 1 to 18 carbon atoms, which may have a linear structure or may be branched.) The α-olefin more preferably has 3 to 12 carbon atoms.
[0026] Specific examples of the structural unit (A) include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene, and may be ethylene. As the ethylene, ethylene derived from a petroleum raw material or a non-petroleum raw material such as a plant raw material can be used. The structural unit (A) may be of one type or of multiple types. Examples of combinations of the two include ethylene-propylene, ethylene-1-butene, ethylene-1-hexene, ethylene-1-octene, propylene-1-butene, propylene-1-hexene, and propylene-1-octene. Examples of combinations of the three include ethylene-propylene-1-butene, ethylene-propylene-1-hexene, ethylene-propylene-1-octene, propylene-1-butene-hexene, and propylene-1-butene-1-octene.
[0027] In the present invention, the structural unit (A) preferably contains ethylene as an essential component and may further contain one or more α-olefins having 3 to 20 carbon atoms, if necessary. The amount of ethylene in the structural unit (A) may be 65 to 100 mol % or 70 to 100 mol % based on the total moles of the structural unit (A). In terms of impact resistance, the structural unit (A) may be a structural unit derived from ethylene.
[0028] (2) Structural unit (B) The structural unit (B) is a structural unit derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group. Note that the structural unit (B) has the same structure as the structural unit derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and as described later in the production method, it does not necessarily have to be produced using a monomer having a carboxyl group and / or a dicarboxylic anhydride group.
[0029] Specific examples of structural units derived from monomers having a carboxyl group include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid, while examples of structural units derived from monomers having a dicarboxylic acid anhydride group include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride, and tetracyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid. 3,6 .0 2,7 ] Unsaturated dicarboxylic acid anhydrides such as dodec-9-ene-4,5-dicarboxylic acid anhydride and 2,7-octadien-1-yl succinic acid anhydride are exemplified. As the structural unit derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, from the viewpoint of industrial availability, preferred examples include acrylic acid, methacrylic acid, and 5-norbornene-2,3-dicarboxylic anhydride, and in particular acrylic acid. Furthermore, the structural unit derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group may be of one type or of multiple types.
[0030] In addition, the dicarboxylic anhydride group may react with moisture in the air to open the ring and become a part of the dicarboxylic acid, but the dicarboxylic anhydride group may be in a ring-opened state as long as it does not deviate from the gist of the present invention.
[0031] (3) Other structural units (C) The copolymer (P) according to the present invention may be a binary copolymer consisting of only the structural unit (A) and the structural unit (B), or a multicomponent copolymer containing the structural unit (A), the structural unit (B), and a structural unit (C) other than the structural unit (A) and the structural unit (B). The multicomponent copolymer may be a multicomponent copolymer containing a structural unit (C) other than the structural unit (A) and the structural unit (B). The monomer that gives the structural unit (C) may be any monomer that is not included in the monomers that give the structural unit (A) and the structural unit (B). The monomer that gives the structural unit (C) is not limited as long as it is a compound having one or more carbon-carbon double bonds in the molecular structure, and may be, for example, an acyclic monomer represented by the general formula (1) or a cyclic monomer represented by the general formula (2). The structural unit (C) may be based on one type of monomer, or may be a combination of two or more types of monomers.
[0032] Acyclic Monomers [ka] [In general formula (1), T 1 ~T 3 each independently represents a substituent selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a hydroxyl group, a hydrocarbon group having 2 to 20 carbon atoms substituted with an alkoxy group having 1 to 20 carbon atoms, a hydrocarbon group having 3 to 20 carbon atoms substituted with an ester group having 2 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a halogen atom, an alkoxy group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an ester group having 2 to 20 carbon atoms, a silyl group having 3 to 20 carbon atoms, a halogen atom, or a cyano group; T 4is a substituent selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms substituted with a hydroxyl group, a hydrocarbon group having 2 to 20 carbon atoms substituted with an alkoxy group having 1 to 20 carbon atoms, a hydrocarbon group having 3 to 20 carbon atoms substituted with an ester group having 2 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a halogen atom, an alkoxy group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an ester group having 2 to 20 carbon atoms, a silyl group having 3 to 20 carbon atoms, a halogen atom, or a cyano group.
[0033] In the ethylene-based ionomer of the present invention, T 1 and T 2 may be a hydrogen atom, T 3 may be a hydrogen atom or a methyl group, T 4 may be an ester group having 2 to 20 carbon atoms.
[0034] T 1 ~T 4 The carbon skeleton of the hydrocarbon group, substituted alkoxy group, substituted ester group, alkoxy group, aryl group, ester group and silyl group may have a branch, a ring, and / or an unsaturated bond. T 1 ~T 4 The lower limit of the number of carbon atoms in the hydrocarbon group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the substituted alkoxy group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the substituted ester group may be 2 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the alkoxy group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4The lower limit of the number of carbon atoms in the aryl group in the above formula may be 6 or more, and the upper limit may be 20 or less, or may be 11 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the ester group may be 2 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The number of carbon atoms in the silyl group in the above formula may be 3 or more, and may be 18 or less, or may be 12 or less. Examples of the silyl group include a trimethylsilyl group, a triethylsilyl group, a tri-n-propylsilyl group, a triisopropylsilyl group, a dimethylphenylsilyl group, a methyldiphenylsilyl group, and a triphenylsilyl group.
[0035] In the ionomer of the present invention, from the viewpoint of ease of production, T 1 and T 2 may be a hydrogen atom, T 3 may be a hydrogen atom or a methyl group, T 1 ~T 3 However, each of them may be a hydrogen atom. In terms of impact resistance, T 4 may be an ester group having 2 to 20 carbon atoms.
[0036] Specific examples of the non-cyclic monomer include T 4 is an ester group having 2 to 20 carbon atoms. T 4 is an ester group having 2 to 20 carbon atoms, the acyclic monomer may be a monomer having the structural formula: CH2=C(R 21 )CO2(R 22 ) where R 21 R is a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, which may have a branch, a ring, and / or an unsaturated bond. 22 is a hydrocarbon group having 1 to 20 carbon atoms, which may have a branch, a ring, and / or an unsaturated bond. 22 It may contain a heteroatom at any position within the group. Structural formula: CH2=C(R 21 )CO2(R 22 ) as a compound represented by R 21 is a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms. 21 is a hydrogen atom, or R 21 Methacrylate esters in which the alkyl group is a methyl group are also included. Structural formula: CH2=C(R 21 )CO2(R 22 Specific examples of the compound represented by the formula (1) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, and benzyl (meth)acrylate. Specific compounds include methyl acrylate, ethyl acrylate, n-butyl acrylate (nBA), isobutyl acrylate (iBA), t-butyl acrylate (tBA), and 2-ethylhexyl acrylate, and may in particular be n-butyl acrylate (nBA), isobutyl acrylate (iBA), and t-butyl acrylate (tBA). The non-cyclic monomer may be of one type or of multiple types.
[0037] Cyclic Monomers [ka] [In general formula (2), R 1 ~R 12may be the same or different and are selected from the group consisting of a hydrogen atom, a halogen atom, and a hydrocarbon group having 1 to 20 carbon atoms; R 9 and R 10 , and R 11 and R 12 may combine together to form a divalent organic group, R 9 or R 10 And, R 11 or R 12 may form a ring together. In addition, n represents 0 or a positive integer, and when n is 2 or more, R 5 ~R 8 may be the same or different in each repeating unit.
[0038] Examples of the cyclic monomer include norbornene-based olefins, such as norbornene, vinylnorbornene, ethylidenenorbornene, norbornadiene, tetracyclododecene, tricyclo[4.3.0.1 2,5 ]dec-3-ene, and the like. Examples of the compound include 2-norbornene (NB) and tetracyclo[6.2.1.13,6.02,7]dodec-4-ene.
[0039] (4) Copolymer (P) The copolymer (P), which is the base resin of the ethylene-based ionomer of the present invention, comprises, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms, and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and may further comprise any structural unit (C) other than the above (A) and (B), which are copolymerized substantially in a linear manner, preferably randomly copolymerized.
[0040] The copolymer according to the present invention must contain at least one type of structural unit (A) and at least one type of structural unit (B), that is, at least two types of monomer units in total, and may also contain another structural unit (C). The structural units and the amounts of the structural units in the copolymer according to the present invention will be described below. A structure derived from one molecule of each of ethylene and / or an α-olefin having 3 to 20 carbon atoms (A), a monomer having a carboxyl group and / or a dicarboxylic anhydride group (B), and an arbitrary monomer (C) is defined as one structural unit in the copolymer. The amount of structural units is the ratio of each structural unit expressed in mol % when all structural units in the copolymer are taken as 100 mol %.
[0041] Amount of structural units of ethylene and / or α-olefin having 3 to 20 carbon atoms (A): The structural unit amount of the structural unit (A) according to the present invention is selected from the following: lower limit is 60.0 mol% or more, preferably 70.0 mol% or more, more preferably 80.0 mol% or more, even more preferably 85.0 mol% or more, still more preferably 90.0 mol% or more, and particularly preferably 92.0 mol% or more, and upper limit is 97.9 mol% or less, preferably 97.5 mol% or less, more preferably 97.0 mol% or less, and even more preferably 96.5 mol% or less. When the amount of structural units derived from ethylene and / or an α-olefin (A) having 3 to 20 carbon atoms is 60.0 mol % or more, the toughness of the copolymer is likely to be high, and when it is 97.9 mol % or less, excessive crystallization of the copolymer is suppressed, and the transparency is likely to be good.
[0042] Amount of structural units of monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group: The amount of the structural unit (B) according to the present invention is selected from the following: the lower limit is 2.0 mol% or more, preferably 2.9 mol% or more, and more preferably 5.1 mol% or more, and the upper limit is 20.0 mol% or less, preferably 15.0 mol% or less, more preferably 10.0 mol% or less, even more preferably 8.0 mol% or less, particularly preferably 6.0 mol% or less, and most preferably 5.6 mol% or less. When the amount of structural units derived from the monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group is 2.0 mol % or more, the copolymer is likely to have sufficient adhesion to different materials with high polarity, and when it is 20.0 mol % or less, the mechanical properties of the copolymer are likely to be good. The monomer having a carboxyl group and / or a dicarboxylic anhydride group may be used alone or in combination of two or more kinds.
[0043] Amount of structural units of any monomer (C): When the ethylene-based ionomer of the present invention contains another structural unit (C), the structural unit amount of the structural unit (C) is selected from the following: the lower limit is 0.001 mol% or more, preferably 0.010 mol% or more, more preferably 0.020 mol% or more, even more preferably 0.1 mol% or more, still more preferably 2.0 mol% or more, and particularly preferably 2.3 mol% or more, and the upper limit is 20.0 mol% or less, preferably 15.0 mol% or less, more preferably 10.0 mol% or less, even more preferably 5.0 mol% or less, and particularly preferably 2.9 mol% or less. When the amount of the structural unit derived from any monomer (C) is 0.001 mol % or more, the flexibility of the copolymer tends to be sufficient, and when it is 20.0 mol % or less, the mechanical properties of the copolymer tend to be sufficient. The optional monomers used may be used alone or in combination of two or more kinds.
[0044] (5) Metal ions Examples of the metal ion in the metal-containing carboxylate to which the carboxyl group and / or dicarboxylic anhydride group is converted include monovalent or divalent metal ions of groups selected from the group consisting of groups 1, 2, and 12 of the periodic table. Specific examples include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and zinc (Zn) ions. From the viewpoint of ease of handling, sodium (Na) or zinc (Zn) ions may be used in particular. The metal-containing carboxylate can be obtained, for example, by hydrolyzing or thermolyzing the ester groups of the copolymer, or by reacting the ester groups with a compound containing a metal ion of Group 1, 2, or 12 of the periodic table while hydrolyzing or thermolyzing the ester groups, thereby converting the ester group portion of the copolymer into a metal-containing carboxylate. The metal ions may be of one type or of multiple types.
[0045] (6) Complex elastic modulus G * Absolute value of = Phase angle δ at 0.1 MPa: In the ethylene-based ionomer of the present invention, the complex modulus G measured by a rotational rheometer * The phase angle δ at the absolute value of =0.1 MPa has a lower limit of 50 degrees or more, preferably 55 degrees or more, and an upper limit of 75 degrees or less, preferably 61 degrees or less. More specifically, the complex modulus G measured by a rotational rheometer * Absolute value of = Phase angle δ at 0.1 MPa (|G * |=0.1 MPa) is 50 degrees or more, the molecular structure of the copolymer is a linear structure that does not contain any long chain branches or a substantially linear structure that contains a small amount of long chain branches that does not affect the mechanical strength. In addition, the complex modulus G measured by a rotational rheometer * Absolute value of = Phase angle δ at 0.1 MPa (|G * If the modulus of elasticity (Tc) is lower than 50 degrees, the molecular structure of the copolymer will contain excessive long chain branches, resulting in poor mechanical strength. Complex modulus G measured by a rotational rheometer * The phase angle δ at the absolute value of Mw / Mn = 0.1 MPa is affected by both the molecular weight distribution and the long chain branching. However, it is an index of the amount of long chain branching only for copolymers with Mw / Mn ≦ 4.0, more preferably Mw / Mn ≦ 3.0, and the more long chain branches there are in the molecular structure, the lower the δ(|G * |=0.1MPa) value is small. If the Mw / Mn of the copolymer is 1.5 or more, the δ(|G *|=0.1MPa) value never exceeds 75 degrees.
[0046] The method for measuring the complex elastic modulus is as follows. The sample is placed in a 1.0 mm thick heat press mold and preheated for 5 minutes in a heat press machine with a surface temperature of 180°C. The residual gas in the molten resin is degassed by repeatedly applying and depressurizing pressure, and then the sample is pressurized to 4.9 MPa and held for 5 minutes. The sample is then transferred to a press machine with a surface temperature of 25°C and cooled by holding at a pressure of 4.9 MPa for 3 minutes to create a press plate made of the sample with a thickness of approximately 1.0 mm. The press plate made of the sample is processed into a circle with a diameter of 25 mm to use as a sample. A Rheometrics ARES type rotational rheometer is used as a measuring device for dynamic viscoelastic properties, and dynamic viscoelasticity is measured under the following conditions in a nitrogen atmosphere. Plate: φ25mm parallel plate ·Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade Complex modulus of elasticity G * logG is the common logarithm of the absolute value (Pa) of * Plot the phase angle δ against logG * = 5.0, the value of δ (degrees) at the point corresponding to δ(|G * |=0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 is calculated by linear interpolation. * If <5.0, logG * Using the three largest values, we plot logG on a quadratic curve * = 5.0.
[0047] (7) Melt flow rate (MFR) at 190°C and a load of 2.16 kg The melt flow rate (MFR) of the ionomer of the present invention at a temperature of 190° C. and a load of 2.16 kg is 0.1 to 30 g / 10 min, and preferably 0.5 to 20 g / 10 min. If the MFR is greater than 30 g / 10 min, the molecular weight will decrease and sufficient elastic recovery will not be obtained.If the MFR is less than 0.1 g / 10 min, the resin pressure during molding, such as injection molding or extrusion molding, will be too high, making molding difficult. The MFR can be increased or decreased by adjusting the molecular weight of the base copolymer (P).
[0048] (8) Elastic recovery rate in tensile tests The elastic recovery rate of the ionomer of the present invention in a tensile test is 65 to 100%, preferably 67 to 100%, and more preferably 69 to 100%. If the elastic recovery rate is less than 65%, the sealing performance of the gasket may decrease during long-term use.
[0049] (9) Tensile modulus The ionomer of the present invention has a tensile modulus of 20 to 350 MPa, preferably 20 to 300 MPa. If the tensile modulus exceeds 350 MPa, the adhesion of the gasket may decrease. On the other hand, an ionomer having a tensile modulus of less than 20 MPa is difficult to produce.
[0050] (10) Tensile impact strength The tensile impact strength of the ionomer of the present invention is 700 KJ / m 2 or more, preferably 800KJ / m 2 Tensile impact strength is 700KJ / m or more. 2 If the gasket is subjected to friction or other stress accompanied by large deformation, it may be damaged. There is no particular upper limit to the tensile impact strength, but in our research, it is set at 2000 KJ / m 2 is considered to be the upper limit.
[0051] (11) Abrasion volume in abrasion test The amount of wear of the ionomer of the present invention in the wear test is less than 10 mg, preferably 9 mg or less, and more preferably 7 mg or less. If the amount of wear in the wear test is 10 mg or more, repeated friction may cause damage to the gasket surface, resulting in leakage of contents and reduced sealing performance.
[0052] 2. Properties of Copolymer (P) Method for measuring the amount of structural units of monomers having carboxyl groups and / or dicarboxylic anhydride groups and optional monomers in copolymers: Number of branches per 1,000 carbons in copolymer: In the copolymer of the present invention, in order to increase the elastic modulus and obtain sufficient mechanical properties, 13 The number of methyl branches calculated by C-NMR may be 50 or less, 5.0 or less, 1.0 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better. The number of ethyl branches may be 3.0 or less, 2.0 or less, 1.0 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better. The number of butyl branches may be 7.0 or less, 5.0 or less, 3.0 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better.
[0053] Method for measuring the amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group and non-cyclic monomers in a copolymer, and the number of branches: The amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group and non-cyclic monomers in the copolymer of the present invention, and the number of branches per 1,000 carbon atoms are 13 It can be determined using C-NMR spectroscopy. 13 C-NMR is measured by the following method.
[0054] 200-300 mg of sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube is sealed after replacing with nitrogen. It is heated and dissolved to prepare a homogeneous solution, which is used as the NMR measurement sample. NMR measurements are performed at 120°C using an AV400M NMR instrument from Bruker Japan Ltd. equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation count of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals are based on this. Obtained 13 In C-NMR, the signals specific to the monomers or branches of the multicomponent copolymer are identified and their intensities are compared, so that the amount of structural units of each monomer in the multicomponent copolymer and the number of branches can be analyzed. The positions of the signals specific to the monomers or branches can be referred to publicly known materials, or can be independently identified depending on the sample. Such an analysis method is commonly known to those skilled in the art.
[0055] Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn): The weight average molecular weight (Mw) of the copolymer according to the present invention has a lower limit of usually 1,000 or more, preferably 100,000 or more, and an upper limit of usually 2,000,000 or less, preferably 1,500,000 or less, more preferably 1,000,000 or less, particularly preferably 800,000 or less, and most preferably 100,000 or less. When the Mw is 1,000 or more, the physical properties such as mechanical strength and impact resistance of the copolymer tend to be good, and when the Mw is 2,000,000 or less, the melt viscosity of the copolymer does not become too high, and the copolymer tends to be easily molded.
[0056] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the copolymer according to the present invention is usually in the range of 1.5 to 4.0, preferably 1.6 to 3.5, and more preferably 1.9 to 2.3. When Mw / Mn is 1.5 or more, the copolymer tends to have good processability in various processes including molding, and when it is 4.0 or less, the copolymer tends to have good mechanical properties. In the present invention, (Mw / Mn) may be expressed as a molecular weight distribution parameter.
[0057] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the copolymer according to the present invention are determined by gel permeation chromatography (GPC). The molecular weight distribution parameter (Mw / Mn) is calculated by determining the number average molecular weight (Mn) by gel permeation chromatography (GPC) and then calculating the ratio of Mw to Mn, Mw / Mn.
[0058] An example of the GPC measurement method according to the present invention is as follows. (Measurement conditions) Machine used: Waters 150C Detector: FOXBORO MIRAN1A IR detector (measurement wavelength: 3.42 μm) Measurement temperature: 140℃ Solvent: orthodichlorobenzene (ODCB) Column: Showa Denko AD806M / S (3 columns) Flow rate: 1.0mL / min Injection volume: 0.2mL (Sample preparation) A 1 mg / mL solution of the sample is prepared using ODCB (containing 0.5 mg / mL BHT (2,6-di-t-butyl-4-methylphenol)), and dissolved at 140° C. for about 1 hour. (Calculation of molecular weight (M)) The standard polystyrene method is used, and the conversion from retention volume to molecular weight is performed using a calibration curve of standard polystyrene that has been prepared in advance. The standard polystyrene used is, for example, Tosoh's (F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, A1000) brand, Showa Denko's monodisperse polystyrene (S-7300, S-3900, S-1950, S-1460, S-1010, S-565, S-152, S-66.0, S-28.5, S-5.05, each 0.07 mg / ml solution), etc. A calibration curve is prepared by injecting 0.2 mL of a solution in which each is dissolved in ODCB (containing 0.5 mg / mL BHT) so that the concentration is 0.5 mg / mL. The calibration curve is a cubic equation obtained by approximating the logarithm of the elution time and molecular weight using a quartic equation, or the calibration curve is a quartic equation obtained by approximating the logarithm of the elution time and molecular weight using a quartic equation. The viscosity equation used for conversion to molecular weight (M) is [η] = K × M α The following values are used: Polystyrene (PS): K = 1.38 x 10 -4 , α=0.7 Polyethylene (PE): K = 3.92 x 10 -4 , α=0.733 Polypropylene (PP): K = 1.03 x 10 -4 , α=0.78
[0059] Melting point (Tm, ℃): The melting point of the copolymer according to the present invention is indicated by the maximum peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). When multiple peaks are shown in the endothermic curve obtained by DSC measurement, with heat flow (mW) on the vertical axis and temperature (°C) on the horizontal axis, the maximum peak temperature refers to the temperature of the peak with the maximum height from the baseline among the multiple peaks, or when there is only one peak, the maximum peak temperature refers to the temperature of that peak. The melting point is preferably 50° C. to 140° C., more preferably 60° C. to 138° C., and most preferably 70° C. to 135° C. If the melting point is 50° C. or higher, the heat resistance is likely to be good, and if it is 140° C. or lower, the adhesiveness is likely to be good. In the present invention, the melting point can be determined from the absorption curve obtained by, for example, using a DSC (DSC7020) manufactured by SII Nano Technology Inc., packing about 5.0 mg of a sample into an aluminum pan, heating it to 200°C at 10°C / min, holding it isothermally at 200°C for 5 minutes, lowering it to 20°C at 10°C / min, holding it isothermally at 20°C for 5 minutes, and then heating it again to 200°C at 10°C / min.
[0060] Crystallinity (%): In the copolymer of the present invention, the crystallinity observed by differential scanning calorimetry (DSC) is not particularly limited, but is preferably more than 0% and not more than 30%, more preferably more than 0% and not more than 25%, particularly preferably 5% or more and not more than 25%, and most preferably 5% or more and not more than 20%. When the crystallinity is more than 0%, the toughness of the copolymer tends to be sufficient, and when the crystallinity is 30% or less, the transparency of the copolymer tends to be good. Note that the crystallinity is an index of transparency, and it can be judged that the lower the crystallinity of the copolymer, the more excellent its transparency. In the present invention, the degree of crystallinity can be determined, for example, by determining the heat of fusion (ΔH) from the area of the melting endothermic peak obtained by a method similar to the above-mentioned method for measuring the melting point, and dividing the heat of fusion by the heat of fusion of perfectly crystalline high-density polyethylene (HDPE), which is 293 J / g.
[0061] Molecular structure of copolymer: The molecular chain terminals of the copolymer according to the present invention may be structural units (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, structural units (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, or structural units (C) of any monomer.
[0062] The copolymer according to the present invention may be a random copolymer, block copolymer, graft copolymer, etc., of a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer. Among these, a random copolymer that can contain a large amount of the structural unit (B) may be used. An example of the molecular structure of a typical ternary copolymer (1) is shown below. A random copolymer is a copolymer in which the probability of finding a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer at a position in an arbitrary molecular chain, as shown in the molecular structure example (1) below, is independent of the type of the adjacent structural unit. As shown below, in the molecular structure example (1) of the copolymer, a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer form a random copolymer.
[0063] [ka]
[0064] For reference, an example of a molecular structure (2) of a copolymer into which structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group has been introduced by graft modification is shown. A part of a copolymer in which structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural unit (C) of an arbitrary monomer are copolymerized is graft modified with structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group.
[0065] [ka]
[0066] Random copolymerization in a copolymer can be confirmed by various methods, but a method for determining random copolymerization from the relationship between the comonomer content and melting point of a copolymer is described in detail in JP 2015-163691 A and JP 2016-079408 A. From the above documents, it can be determined that randomness is low when the melting point (Tm, °C) of the copolymer is higher than -3.74 × [Z] + 130 (where [Z] is the comonomer content / mol%).
[0067] The copolymer according to the present invention, which is a random copolymer, preferably has a melting point (Tm, °C) measured by differential scanning calorimetry (DSC) and a total content [Z] (mol %) of the structural unit (B) of the monomer having a carboxyl group and / or a dicarboxylic anhydride group and the structural unit (C) of an arbitrary monomer, which satisfy the following formula (I): 50 < Tm < -3.74×[Z]+130 (I) When the melting point of the copolymer (Tm, °C) is lower than -3.74 × [Z] + 130 (°C), the copolymer has a high degree of random copolymerization, and therefore mechanical properties such as impact strength tend to be good. When the melting point is higher than 50°C, the copolymer tends to have good heat resistance.
[0068] Furthermore, the copolymer according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making the molecular structure thereof linear. It is known that the molecular structure of the copolymer varies depending on the production method, such as polymerization by a high-pressure radical polymerization process or polymerization using a metal catalyst. The difference in molecular structure can be controlled by selecting the production method, but the molecular structure can also be estimated from the complex modulus measured with a rotational rheometer, as described in JP 2010-150532 A, for example.
[0069] Complex modulus of elasticity G * Absolute value of = Phase angle δ at 0.1 MPa: In the copolymer according to the present invention, the complex modulus G measured by a rotational rheometer* The phase angle δ at the absolute value of 0.1 MPa may have a lower limit of 50 degrees or more, 51 degrees or more, 54 degrees or more, 56 degrees or more, or 58 degrees or more, and an upper limit of 75 degrees or less, or 70 degrees or less. Complex modulus of elasticity G * The phase angle δ at the absolute value of 0.1 MPa can be measured by the same method as described for the ethylene-based ionomer.
[0070] 3. Preparation of copolymer (P) The copolymer (P) according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making its molecular structure linear. Polymerization catalyst The type of polymerization catalyst used in the production of the copolymer according to the present invention is not particularly limited as long as it is capable of copolymerizing the structural unit (A), the structural unit (B), and the optional structural unit (C). For example, a transition metal compound of Groups 5 to 11 having a chelating ligand can be mentioned. Specific examples of preferred transition metals include vanadium atom, niobium atom, tantalum atom, chromium atom, molybdenum atom, tungsten atom, manganese atom, iron atom, platinum atom, ruthenium atom, cobalt atom, rhodium atom, nickel atom, palladium atom, copper atom, etc. Among these, preferred are transition metals of Groups 8 to 11, more preferred are transition metals of Group 10, and particularly preferred are nickel (Ni) and palladium (Pd). These metals may be used alone or in combination. Chelating ligands have at least two atoms selected from the group consisting of P, N, O, and S, and include ligands that are bidentate or multidentate, and are electronically neutral or anionic. Exemplary chelating ligand structures are given in the review by Brookhart et al. (Chem. Rev., 2000, 100, 1169). The chelating ligand preferably includes a bidentate anionic P, O ligand. Examples of the bidentate anionic P, O ligand include phosphorus sulfonic acid, phosphorus carboxylic acid, phosphorus phenol, and phosphorus enolate. Other examples of the chelating ligand include a bidentate anionic N, O ligand. Examples of the bidentate anionic N, O ligand include salicylaldiminate and pyridine carboxylic acid. Other examples of the chelating ligand include a diimine ligand, a diphenoxide ligand, and a diamide ligand. Among these, the chelating ligand is preferably phosphorus sulfonic acid or phosphorus phenol.
[0071] The structure of the metal complex obtained from the chelating ligand is represented by the following structural formula (a) or (b) in which an arylphosphine compound, an arylarsine compound or an arylantimony compound which may have a substituent is coordinated.
[0072] [ka]
[0073] [ka]
[0074] [In structural formula (a) and structural formula (b), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1 represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 56 and R 57 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R 52 )2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51 ) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 56 and R 57 may be linked to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur, in which case the ring has 5 to 8 members and may or may not have a substituent on the ring. L 1 represents a ligand coordinated to M. Also, R 53 and L1 may be bonded to each other to form a ring.
[0075] The structure of the metal complex obtained from the chelating ligand is more preferably a transition metal complex represented by the following structural formula (c). [ka]
[0076] [In structural formula (c), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1 represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 58 , R 59 , R 60 and R 61 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R52 )2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51 ) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 58 ~R 61 may be bonded to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur. In this case, the number of ring members is 5 to 8, and the ring may or may not have a substituent. L 1 represents a ligand coordinated to M. Also, R 53 and L 1 may be bonded to each other to form a ring.
[0077] Here, typical catalysts of Group 5 to 11 transition metal compounds having a chelating ligand include so-called SHOP catalysts and Drent catalysts. The SHOP catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to nickel metal (see, for example, International Publication No. 2010-050256). Furthermore, the Drent catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to palladium metal (see, for example, JP-A-2010-202647).
[0078] Copolymerization method: The polymerization method for the copolymer according to the present invention is not limited. Examples of the polymerization method include slurry polymerization in which at least a portion of the produced polymer becomes a slurry in a medium, bulk polymerization in which the liquefied monomer itself is used as the medium, gas phase polymerization in vaporized monomer, and high pressure ionic polymerization in which at least a portion of the produced polymer is dissolved in monomer liquefied at high temperature and pressure. The polymerization method may be any of batch polymerization, semi-batch polymerization, and continuous polymerization. Furthermore, living polymerization may be carried out, or polymerization may be carried out while simultaneously causing chain transfer. Furthermore, during polymerization, a so-called chain shuttling agent (CSA) may be used in combination to carry out a chain shuttling reaction or coordinate chain transfer polymerization (CCTP). Specific manufacturing processes and conditions are disclosed in, for example, Japanese Patent Application Laid-Open Nos. 2010-260913 and 2010-202647.
[0079] Method for introducing carboxyl groups and / or dicarboxylic anhydride groups into copolymers: The method for introducing a carboxyl group and / or a dicarboxylic anhydride group into the copolymer according to the present invention is not particularly limited. Carboxyl groups and / or dicarboxylic anhydride groups can be introduced by various methods within the scope of the present invention. Examples of methods for introducing a carboxyl group and / or a dicarboxylic anhydride group include a method of directly copolymerizing a comonomer having a carboxyl group and / or a dicarboxylic anhydride group, and a method of copolymerizing another monomer and then introducing a carboxyl group and / or a dicarboxylic anhydride group by modification.
[0080] Methods for introducing a carboxyl group and / or a dicarboxylic anhydride group by modification include, for example, when introducing a carboxylic acid, a method in which an acrylic ester is copolymerized and then hydrolyzed to convert it to a carboxylic acid, and a method in which t-butyl acrylate is copolymerized and then thermally decomposed to convert it to a carboxylic acid.
[0081] A conventionally known acid-base catalyst may be used as an additive for promoting the reaction during the hydrolysis or thermal decomposition. The acid-base catalyst is not particularly limited, and examples of the acid-base catalyst that can be used include, for example, hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, alkali metals or carbonates of alkaline earth metals such as sodium hydrogencarbonate or sodium carbonate, solid acids such as montmorillonite, inorganic acids such as hydrochloric acid, nitric acid, or sulfuric acid, and organic acids such as formic acid, acetic acid, benzoic acid, citric acid, paratoluenesulfonic acid, trifluoroacetic acid, or trifluoromethanesulfonic acid. From the viewpoints of reaction promotion effect, cost, equipment corrosivity, etc., sodium hydroxide, potassium hydroxide, sodium carbonate, paratoluenesulfonic acid, and trifluoroacetic acid are preferred, and paratoluenesulfonic acid and trifluoroacetic acid are more preferred.
[0082] 4. Production of ethylene-based ionomers The ethylene-based ionomer of the present invention is an ionomer having a substantially linear structure in which at least a part of the carboxyl group and / or dicarboxylic anhydride group of the structural unit (B) in the copolymer (P) is converted to a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table. As described below, the ionomer is obtained by reacting a metal salt with the copolymer (P) that becomes the ionomer base resin, and during this process, a reaction that cuts the molecular chain of the polymer does not usually occur. Therefore, parameters related to the structure, such as the molar ratio of the comonomer, the degree of branching, and randomness, are usually preserved between the ionomer base resin and the ionomer.
[0083] Melting point of ionomer (Tm, ℃) The melting point (Tm, ° C.) of the ionomer of the present invention is preferably 50° C. to 140° C., more preferably 60° C. to 138° C., and most preferably 70° C. to 135° C. If it is within this range, the heat resistance and adhesiveness tend to be good. Of the ionomers related to the present invention, ionomers based on a binary copolymer consisting of only structural units (A) and (B) preferably have a melting point of 90° C. or higher, more preferably 95° C. or higher, and even more preferably 100° C. or higher. Ionomers based on ternary or higher multi-component copolymers preferably have a melting point of less than 100° C., more preferably less than 95° C., and even more preferably less than 90° C.
[0084] Crystallinity (%) In the ionomer of the present invention, the crystallinity observed by differential scanning calorimetry (DSC) is not particularly limited, but is preferably more than 0% and not more than 30%, more preferably more than 0% and not more than 25%, particularly preferably more than 5% and not more than 25%, and most preferably 7% or more and not more than 24%. When the crystallinity is within this range, the toughness and transparency of the ionomer tend to be good. Note that the crystallinity is an index of transparency, and it can be determined that the lower the crystallinity of the ionomer, the more excellent its transparency.
[0085] Metal ions The metal ion in the metal-containing carboxylate to which the carboxyl group and / or dicarboxylic anhydride group is converted may be a monovalent or divalent metal ion of Group 1, Group 2, or Group 12 of the periodic table, preferably Li + , Na + , K + , Rb + , Cs + , Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ More preferably, at least one selected from the group consisting of Li + , Na+ , K + , Mg 2+ , Ca 2+ , and Zn 2+ , more preferably Na + , and Zn 2+ At least one selected from the group consisting of: Two or more of these metal ions may be mixed and contained as necessary.
[0086] ·Neutralization degree (mol%) The metal ion content is preferably an amount that neutralizes at least a part or all of the carboxyl groups and / or dicarboxylic anhydride groups in the copolymer as the base polymer, and the preferred degree of neutralization (average degree of neutralization) is 5 to 95 mol%, more preferably 10 to 90 mol%, even more preferably 20 to 80 mol%, and most preferably 10 to 40 mol%. The degree of neutralization can be determined from the ratio of the total molar amount of the valence×molar amount of the metal ion to the total molar amount of the carboxy groups that may be contained in the carboxy groups and / or dicarboxylic anhydride groups in the copolymer. When a dicarboxylic anhydride group forms a carboxylate, it opens its ring to form a dicarboxylic acid, so the total molar amount of the carboxyl groups is calculated assuming that there are 2 mol of carboxyl groups per 1 mol of dicarboxylic anhydride group. 2+ For divalent metal ions such as those mentioned above, 1 mole of each can form a salt with 2 moles of carboxyl groups, and the total molar amount of the molecule is calculated using 2 x the molar amount. A high degree of neutralization results in an ionomer with high tensile strength and tensile stress at break, and low tensile strain at break, but the melt flow rate (MFR) of the ionomer tends to be low. On the other hand, a low degree of neutralization results in an ionomer with a moderate MFR, but low tensile modulus and tensile stress at break, and high tensile strain at break. The degree of neutralization can be calculated from the amount of carboxyl groups and / or dicarboxylic anhydride groups and the molar ratio of the added metal ions.
[0087] -Production method of ethylene ionomer The ionomer according to the present invention may be obtained by treating a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and a monomer having a carboxyl group and / or a dicarboxylic anhydride group, obtained by the above-mentioned method for introducing a carboxyl group and / or a dicarboxylic anhydride group into the copolymer, with a metal salt containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table, to convert the copolymer into a metal-containing carboxylate. The ionomer according to the present invention may also be obtained by heating a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylate, to convert at least a part of the ester groups in the copolymer into a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table, to convert the copolymer into a metal-containing carboxylate.
[0088] When an ionomer is produced after introducing a carboxyl group and / or a dicarboxylic anhydride group into the former polymer, the production method is, for example, as follows: That is, a metal ion source is prepared by kneading a metal salt with a substance that captures metal ions, such as an ethylene / methacrylic acid (MAA) copolymer, optionally with heating, and then the metal ion source is added to the copolymer (P) that becomes the ionomer base resin in an amount that results in a desired degree of neutralization, and kneaded to obtain the ionomer.
[0089] In the latter thermal conversion step, (i) a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid ester may be heated to obtain a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid by hydrolysis or thermal decomposition, and then the copolymer may be reacted with a compound containing a metal ion of Group 1, Group 2, or Group 12 of the periodic table to convert the carboxylic acid in the copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid to the metal-containing carboxylate; or (ii) a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid ester may be heated to hydrolyze or thermally decompose the ester group of the copolymer while reacting with a compound containing a metal ion of Group 1, Group 2, or Group 12 of the periodic table to convert the ester group portion in the copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid ester to the metal-containing carboxylate.
[0090] Furthermore, the compound containing a metal ion may be an oxide, hydroxide, carbonate, bicarbonate, acetate, formate, etc. of a metal of Group 1, 2, or 12 of the periodic table. The compound containing metal ions may be supplied to the reaction system in the form of particles or fine powder, or may be dissolved or dispersed in water or an organic solvent and then supplied to the reaction system, or a master batch may be prepared using an ethylene / unsaturated carboxylic acid copolymer or an olefin copolymer as a base polymer and then supplied to the reaction system. In order to ensure smooth reaction, it is preferable to prepare a master batch and supply it to the reaction system.
[0091] Furthermore, the reaction with the compound containing metal ions may be carried out by melt kneading using various types of equipment such as a vent extruder, a Banbury mixer, a roll mill, etc., and the reaction may be a batch or continuous method. Since the reaction can be carried out smoothly by discharging water and carbon dioxide gas by-produced by the reaction using a degassing device, it is preferable to carry out the reaction continuously using an extruder equipped with a degassing device such as a vent extruder. In the reaction with the compound containing metal ions, a small amount of water may be injected to promote the reaction.
[0092] The temperature at which the copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms and an unsaturated carboxylic acid ester is heated may be any temperature at which the ester becomes a carboxylic acid, and if the heating temperature is too low, the ester is not converted to a carboxylic acid, whereas if the heating temperature is too high, decarbonylation or decomposition of the copolymer may proceed. Therefore, the heating temperature in the present invention is preferably in the range of 80°C to 350°C, more preferably 100°C to 340°C, even more preferably 150°C to 330°C, and even more preferably 200°C to 320°C.
[0093] The reaction time varies depending on the heating temperature, the reactivity of the ester group portion, etc., but is usually 1 minute to 50 hours, more preferably 2 minutes to 30 hours, even more preferably 2 minutes to 10 hours, still more preferably 2 minutes to 3 hours, and particularly preferably 3 minutes to 2 hours.
[0094] In the above steps, the reaction atmosphere is not particularly limited, but it is generally preferable to carry out the reaction under an inert gas flow. Examples of the inert gas include nitrogen, argon, and carbon dioxide. A small amount of oxygen or air may be mixed in.
[0095] The reactor used in the above step is not particularly limited, and any method can be used as long as it can substantially uniformly stir the copolymer. A glass vessel or an autoclave (AC) equipped with a stirrer may be used, or any conventionally known kneading machine such as a Brabender plastograph, a single-screw or twin-screw extruder, a high-intensity screw-type kneader, a Banbury mixer, a kneader, or a roll may be used.
[0096] Whether or not a metal ion has been introduced into an ionomer-based resin and it has become an ionomer can be confirmed by measuring the IR spectrum of the resulting resin and examining the decrease in the peak derived from the carbonyl group of the carboxylic acid (dimer). Similarly, the degree of neutralization can be confirmed by calculating from the molar ratio described above, as well as examining the decrease in the peak derived from the carbonyl group of the carboxylic acid (dimer) and the increase in the peak derived from the carbonyl group of the carboxylate salt group.
[0097] 5.Resin composition The ethylene-based ionomer of the present invention may be used alone or as a resin composition containing other resin components. Hereinafter, when used in a molded product, the term "resin composition containing an ethylene-based ionomer" includes the ethylene-based ionomer alone or a composition containing other resin components or additives. The other resin components are not particularly limited as long as they are compatible with the ethylene-based ionomer and do not impair the effects of the present invention. For example, high density polyethylene, medium density polyethylene, low density polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid ester copolymer, other ionomers, etc. can be mentioned. Two or more types of materials can also be used in combination. The amount of these resin components is not particularly limited as long as it does not impair the effects of the present invention.
[0098] Examples of additives to be blended into the resin composition include conventionally known antioxidants, ultraviolet absorbers, lubricants, antistatic agents, colorants, pigments, crosslinking agents, foaming agents, nucleating agents, flame retardants, conductive materials, and fillers.
[0099] The content of the ethylene-based ionomer in the resin composition is preferably 10% by weight or more, more preferably 30% by weight or more, further preferably 50% by weight or more, and particularly preferably 60% by weight or more. The upper limit can be arbitrarily selected from 100% by weight or less, 90% by weight or less, and 70% by weight or less. The higher the content of the ethylene-based ionomer of the present invention in the resin composition, the more fully it becomes possible to exhibit the excellent physical properties and the like that are achieved by using the ionomer, but the blending amount can be selected as desired from the standpoints of other processability, required physical properties, cost, and the like.
[0100] The method for producing the resin composition is not particularly limited, but for example, the ethylene-based ionomer of the present invention is dry-blended with other resin components, various additives, and the like using a Henschel mixer, a super mixer, a tumbler-type mixer, or the like, and then the mixture is heated and kneaded using a single-screw or twin-screw extruder, a kneader, a pelletizer, a homogenizer, or the like, and extruded to prepare pellets, thereby obtaining a resin composition.
[0101] 6. Molded body The ethylene-based ionomer alone or a resin composition containing the ethylene-based ionomer can be pelletized in a conventional manner and then molded into a desired molded product using various molding machines. As a molding method, various molding methods in injection molding or compression molding, such as low pressure molding, injection compression molding, gas-assisted molding, two-color molding, and in-mold molding, can be used. The conditions for injection molding or compression molding are not particularly limited, but conventionally known conditions can be used using conventionally known molding devices. Molded articles of the ethylene-based ionomer alone or of the resin composition containing the ethylene-based ionomer have an excellent balance of flexibility, elastic recovery, impact resistance and abrasion resistance, and can be used as bottle cap closure liners, gaskets for sealing parts of electronic devices, etc. EXAMPLES
[0102] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured and evaluated by the methods shown below. In the table, "no data" means that no measurement was performed, and "not detected" means that the value was below the detection limit.
[0103] <Measurement and Evaluation> (1) Complex elastic modulus G * Measurement of phase angle δ at absolute value of = 0.1 MPa 1) Sample preparation and measurement The sample was placed in a 1.0 mm thick mold for hot pressing, preheated in a hot press machine with a surface temperature of 180°C for 5 minutes, and then repeatedly pressurized and depressurized to remove residual gas in the molten resin. The sample was then pressed at 4.9 MPa and held for 5 minutes. The sample was then transferred to a press machine with a surface temperature of 25°C and cooled by holding at a pressure of 4.9 MPa for 3 minutes to produce a pressed plate made of a sample with a thickness of approximately 1.0 mm. The pressed plate made of the sample was processed into a circular shape with a diameter of 25 mm to prepare a sample. The dynamic viscoelasticity was measured under the following conditions in a nitrogen atmosphere using an ARES type rotational rheometer manufactured by Rheometrics Co., Ltd. as a measuring device for dynamic viscoelastic properties. Plate: φ25mm (diameter) parallel plate ·Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade Complex modulus of elasticity G * logG is the common logarithm of the absolute value (Pa) of * Plot the phase angle δ against logG * = 5.0, the value of δ (degrees) at the point corresponding to δ(|G * |=0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 was calculated by linear interpolation. * If <5.0, logG * Using the three largest values, we plot logG on a quadratic curve * The δ value at =5.0 was extrapolated.
[0104] (2) Measurement of weight average molecular weight (Mw) and molecular weight distribution parameter (Mw / Mn) The weight average molecular weight (Mw) was determined by gel permeation chromatography (GPC). The molecular weight distribution parameter (Mw / Mn) was calculated from the ratio of Mw to Mn, Mw / Mn, obtained by further determining the number average molecular weight (Mn) by gel permeation chromatography (GPC). The measurements were carried out according to the following procedures and conditions.
[0105] 1) Sample pretreatment When the sample contained a carboxylic acid group, it was subjected to an esterification treatment, such as methyl esterification using diazomethane or trimethylsilyl (TMS) diazomethane, before use in the measurement. When the sample contained a carboxylate group, it was subjected to an acid treatment to modify the carboxylate group to a carboxylic acid group, and then subjected to the above-mentioned esterification treatment before use in the measurement.
[0106] 2) Preparation of sample solution 3 mg of sample and 3 mL of o-dichlorobenzene were weighed into a 4 mL vial, and the vial was capped with a screw cap and a Teflon (registered trademark) septum, and then shaken for 2 hours at 150°C using a Senshu Scientific SSC-7300 high-temperature shaker. After shaking, it was visually confirmed that there were no insoluble components.
[0107] 3) Measurement A Waters Alliance GPCV2000 was connected to Showa Denko's high temperature GPC columns Showdex HT-G x 1 and HT-806M x 2, and measurements were performed using o-dichlorobenzene as the eluent at a temperature of 145°C and a flow rate of 1.0 mL / min.
[0108] 4) Calibration curve The column was calibrated using monodisperse polystyrene (S-7300, S-3900, S-1950, S-1460, S-1010, S-565, S-152, S-66.0, S-28.5, S-5.05, each 0.07 mg / ml solution) manufactured by Showa Denko, n-eicosane and n-tetracontane were measured under the same conditions as above, and the elution time and the logarithm of the molecular weight were approximated by a fourth-order equation.PS ) and polyethylene molecular weight (M PE The following formula was used to convert M PE =0.468×M PS
[0109] (3) Melt flow rate (MFR) The MFR was measured in accordance with Table 1-Condition 7 of JIS K-7210 (1999) at a temperature of 190°C and a load of 2.16 kg.
[0110] (4) Tensile modulus A 1 mm thick sheet was prepared as a sample by the method described in JIS K7151 (1995) (cooling method A), and this was punched out to prepare a small 5B type test piece described in JIS K7162 (1994). A tensile test was performed at a temperature of 23°C in accordance with JIS K7161 (1994) to measure the tensile modulus of elasticity. The test speed was 10 mm / min.
[0111] (5) Melting point and crystallinity The melting point is indicated by the peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). The measurement was performed using a DSC (DSC7020) manufactured by SII Nano Technology Co., Ltd. under the following measurement conditions. Approximately 5.0 mg of the sample was packed into an aluminum pan, heated to 200°C at 10°C / min, held at 200°C for 5 minutes, and then cooled to 30°C at 10°C / min. After holding at 30°C for 5 minutes, the sample was again heated at 10°C / min. The maximum peak temperature in the absorption curve was taken as the melting point Tm, and the heat of fusion (ΔH) was calculated from the area of the melting endothermic peak. The degree of crystallinity (%) was calculated by dividing the heat of fusion by the heat of fusion of perfect crystals of high density polyethylene (HDPE), 293 J / g.
[0112] 6) Method for measuring the amount of structural units derived from monomers having a carboxyl group and / or a dicarboxylic anhydride group, and non-cyclic monomers, and the number of branches per 1,000 carbons The amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group and non-cyclic monomers in the multicomponent copolymer of the present invention, and the number of branches per 1,000 carbon atoms are 13 It can be determined using C-NMR spectroscopy. 13 C-NMR was measured by the following method. 200-300 mg of sample was placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube was purged with nitrogen, sealed, and heated to dissolve and prepare a homogeneous solution to be used as the NMR measurement sample. NMR measurements were performed at 120°C using an AV400M NMR instrument from Bruker Japan equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation number of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals were based on this.
[0113] 1) Sample pretreatment When the sample contained a carboxylate group, the sample was subjected to an acid treatment to convert the carboxylate group to a carboxyl group before the measurement. When the sample contained a carboxyl group, an esterification treatment such as methyl esterification using diazomethane or trimethylsilyl (TMS) diazomethane may be appropriately performed.
[0114] 2) Calculation of the amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group, and non-cyclic monomers <e tba> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 It is detected at 79.6 to 78.8 in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(E)〕 Here, I(tBA) and I(E) are the quantities shown in the following formulas. I(tBA)=I 79.6~78.8 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(tBA) × 7) / 2
[0115] <e tba nba> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 The methylene signal of the butoxy group of nBA was detected at 64.1 to 63.4 ppm in the C-NMR spectrum and 79.6 to 78.8 ppm in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(nBA) + I(E)〕 Total amount of nBA (mol%)=I(nBA)×100 / [I(tBA)+I(nBA)+I(E)] Here, I(tBA), I(nBA), and I(E) are quantities expressed by the following formulas, respectively. I(tBA)=I 79.6~78.8 I(nBA)=I 64.1~63.4 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(nBA) x 7 -I(tBA) x 7) / 2
[0116] <e tba iba> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 The methylene signal of the isobutoxy group of iBA is detected at 70.5 to 69.8 ppm, and the methyl signal of the isobutoxy group is detected at 19.5 to 18.9 ppm in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(iBA) + I(E)〕 Total amount of iBA (mol%)=I(iBA)×100 / [I(tBA)+I(iBA)+I(E)] Here, I(tBA), I(iBA), and I(E) are quantities expressed by the following formulas, respectively. I(tBA)=I 79.6~78.8 I(iBA) = (I 70.5~69.8 +I 19.5~18.9 ) / 3 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(iBA) x 7 -I(tBA) x 7) / 2
[0117] <e tba nb> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 The methine carbon signal of NB was detected at 41.9 to 41.1 ppm in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(NB) + I(E)〕 Total amount of NB (mol%) = I(NB) × 100 / 〔I(tBA) + I(NB) + I(E)〕 Here, I(tBA), I(NB), and I(E) are quantities expressed by the following formulas. I(tBA)=I 79.6~78.8 I(NB)=(I 41.9~41.1 ) / 2 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(NB) x 7 -I(tBA) x 7) / 2
[0118] In addition, when the structural unit amount of each monomer is indicated by "<0.1" including an inequality sign, it means that it is present as a structural unit in the multi-component copolymer, but the amount is less than 0.1 mol %, taking into account significant digits.
[0119] 3) Calculation of the number of branches per 1,000 carbon atoms Multicomponent copolymers include isolated types in which a branch exists alone in the main chain, complex types (face-to-face types in which branches face each other via the main chain, branched-branch types in which branches exist within branched chains, and chain types). The following is an example of the structure of an ethyl branch. In the example of the facing type, R represents an alkyl group.
[0120] [ka]
[0121] The number of branches per 1,000 carbons is calculated by substituting either I(B1), I(B2), or I(B4) below into the I (branch) term in the following formula. B1 represents methyl branches, B2 represents ethyl branches, and B4 represents butyl branches. The number of methyl branches is calculated using I(B1), the number of ethyl branches using I(B2), and the number of butyl branches using I(B4). Number of branches (per 1,000 carbons) = I (branches) x 1000 / I (total) Here, I(total), I(B1), I(B2), and I(B4) are quantities expressed by the following formulas. I(total)=I 180.0~135.0 +I 120.0~5.0 I(B1)=(I 20.0~19.8 +I 33.2~33.1 +I 37.5~37.3 ) / 4 I(B2)=I 8.6~7.6 +I 11.8~10.5 I(B4)=I 14.3~13.7 -I 32.2~32.0 Here, I is the integrated intensity, and the subscripts of I indicate the range of chemical shifts. For example, I 180.0~135.0 was detected between 180.0 ppm and 135.0 ppm. 13 C The integrated intensity of the signal is shown. The attribution was based on the non-patent literature Macromolecules 1984, 17, 1756-1761 and Macromolecules 1979, 12, 41. In addition, when each branch number is indicated by "<0.1" including an inequality sign, it means that it exists as a structural unit in the multi-component copolymer, but the amount is less than 0.1 mol% considering significant figures. Also, "not detected" means below the detection limit.
[0122] (7) Infrared absorption spectrum The sample was melted at 180° C. for 3 minutes and compression molded to prepare a film with a thickness of about 50 μm. This film was analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum. Product name: FT / IR-6100 manufactured by JASCO Corporation Measurement method: transmission method Detector: TGS (Triglycine sulfate) Number of times: 16 to 512 Resolution: 4.0cm -1 Measurement wavelength: 5000~500cm -1
[0123] (8) Tensile impact strength 1) Preparation of tensile impact strength test samples The sample was placed in a 1 mm thick mold for hot pressing, preheated for 5 minutes in a hot press machine with a surface temperature of 180 ° C., and then repeatedly pressurized and depressurized to melt the sample and degas the residual gas in the sample. The sample was then pressurized at 4.9 MPa and held for 5 minutes. After that, the sample was gradually cooled at a rate of 10 ° C. / min while still under a pressure of 4.9 MPa, and the press plate was removed from the mold when the temperature had dropped to near room temperature. The obtained press plate was conditioned for 48 hours or more in an environment with a temperature of 23 ± 2 ° C. and a humidity of 50 ± 5 ° C. A test piece in the shape of ASTM D1822 Type-S was punched out from the conditioned press plate to prepare a tensile impact strength test sample.
[0124] 2) Tensile impact strength test The tensile impact strength was measured using the above test pieces with reference to JIS K 7160-1996 B method. The only difference from JIS K 7160-1996 was the shape of the test pieces. Other measurement conditions were performed in accordance with JIS K 7160-1996.
[0125] (9) Measurement of wear 1) Preparation of wear test samples The sample was placed in a mold for hot pressing with dimensions: 150 mm x 150 mm, thickness 1 mm, and preheated for 5 minutes in a hot press machine with a surface temperature of 180 ° C., and then the sample was melted and the residual gas in the sample was degassed by repeatedly applying pressure and reducing pressure, and the sample was further pressurized at 4.9 MPa and held for 3 minutes. After that, the sample was gradually cooled at a rate of 10 ° C. / min while applying a pressure of 4.9 MPa, and the pressed plate was removed from the mold when the temperature had dropped to near room temperature. The obtained pressed plate was conditioned for 48 hours or more in an environment with a temperature of 23 ± 2 ° C. and a humidity of 50 ± 5 ° C. The conditioned pressed plate was cut into a circle with a diameter of about 115 mm, and a hole with a diameter of about 6.5 mm was drilled in the center to prepare a wear test sample.
[0126] 2) Abrasion test conditions Using the above test sample, the amount of wear loss (mg) was measured under the following conditions in accordance with JIS K 7204-1999, and this was taken as the amount of wear. · Equipment: Taber abrasion tester (rotary abrasion tester) manufactured by Toyo Seiki Seisakusho Co., Ltd. ·Wear wheel: CS-17 Rotational speed: 60 rpm Test count: 1000 rotations Load: 4.9N
[0127] (10) Elastic recovery 1) Preparation of test specimens A sheet having a thickness of 1 mm was prepared from the sample using the method described in JIS K7151 (1995) (cooling method A), and this was punched out to prepare a small test piece of type 5B described in JIS K7162 (1994). 2) Elastic recovery rate measurement The initial grip distance of the tensile tester Tensilon RTG-1250 (manufactured by A & D Co., Ltd.) was set to 21 mm, and a 5B-type small test piece was attached and marked on the top and bottom of the test piece. The grip distance was set to B, and the tester was raised at a speed of 10 mm / min until B reached approximately 24 mm, after which it was stopped and held in that state for 1 minute. The lower grip was then released and the test piece was allowed to contract for 3 minutes. The test piece was removed from the tester, and the distance between the marks on the top and bottom of the test piece before the grips were raised was set as the grip distance C after the test, and C (mm) was measured. The elastic recovery rate was calculated from the above A, B, and C using the following formula. Elastic recovery rate (%) = {1-(distance between grippers after test C-initial distance between grippers A) / displacement of grippers B)} x 100 The test conditions were a temperature of 23°C and a relative humidity of 50%.
[0128] <Synthesis of metal complexes> (1) Synthesis of B-27DM / Ni complex The B-27DM / Ni complex was prepared according to Synthesis Example 4 described in WO 2010 / 050256, using the following 2-bis(2,6-dimethoxyphenyl)phosphano-6-pentafluorophenylphenol ligand (B-27DM). A nickel complex (B-27DM / Ni) was synthesized in which B-27DM and Ni(COD)2 reacted in a 1:1 ratio using bis(1,5-cyclooctadiene)nickel(0) (referred to as Ni(COD)2) according to Example 1 of WO 2010 / 050256. [ka]
[0129] (2) Synthesis of B-423 / Ni complex 1) Ligand B-423: Synthesis of 2-bis(2,6-dimethoxyphenyl)phosphano-6-(2,6-diisopropylphenyl)phenol [ka] Ligand B-423 was synthesized according to the following scheme. In the following chemical formulas, -OMOM represents a methoxymethoxy group (-OCH2OCH3).
[0130] [ka]
[0131] (i) Synthesis of Compound 2 Synthesised according to WO 2010 / 050256.
[0132] (ii) Synthesis of Compound 3 To a solution of compound 2 (2.64 g, 10.0 mmol) in THF (5.0 ml) was added i-PrMgCl (2 M, 5.25 ml) at 0° C. The reaction mixture was stirred at 25° C. for 1 h, and then PCl (618 mg, 4.50 mmol) was added at −78° C. The reaction mixture was warmed to 25° C. over 3 hours to give a yellow suspension. The solvent was removed under reduced pressure to give a yellow solid. This mixture was used in the next reaction without purification.
[0133] (iii) Synthesis of Compound 5 To a solution of compound 4 (30 g, 220 mmol) in THF (250 ml), n-BuLi (2.5 M, 96 ml) was added at 0°C and stirred at 30°C for 1 hour. To this solution, B(OiPr)3 (123 g, 651 mmol) was added at -78°C and stirred at 30°C for 2 hours to obtain a white suspension. Hydrochloric acid (1 M) was added to adjust the pH to 6-7, and the organic layer was concentrated to obtain a mixture. The obtained mixture was washed with petroleum ether (80 ml) to obtain 26 g of compound 5.
[0134] (iv) Synthesis of Compound 7 Compound 5 (5.00g, 27.5mmol), compound 6 (4.42g, 18.3mmol), Pd2(dba)3 (168mg, 0.183mmol), s-Phos (2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl) (376mg, 0.916mmol), and K3PO4 (7.35g, 34.6mmol) were weighed into a reaction vessel, and toluene (40ml) was added. This solution was reacted at 110°C for 12 hours to obtain a black suspension. H2O (50ml) was added, and the mixture was extracted with EtOAc (55ml x 3). The organic layer was washed with brine (20ml) and dehydrated with Na2SO4. The organic layer was filtered and the solvent was removed under reduced pressure, and then purified with a silica gel column to obtain 1.3g of an oily substance.
[0135] (v) Synthesis of compound 8 n-BuLi (2.5M, 9.15ml) was added dropwise to a solution of compound 7 (6.5g, 22mmol) in THF (40ml) at 0°C, and the mixture was heated to 30°C and stirred for 1 hour. The reaction solution was cooled to -78°C, CuCN (2.1g, 23mmol) was added, and the mixture was stirred at 30°C for 1 hour. The reaction solution was cooled to -78°C, a solution of compound 3 (6.7g, 20mmol) in THF (40ml) was added, and the mixture was stirred at 30°C for 12 hours to obtain a white suspension. When H2O (50ml) was added to the suspension, a white precipitate was formed. The white precipitate was collected by filtration and dissolved in dichloromethane (20ml), and ammonia water (80ml) was added and stirred for 3 hours. The product was extracted with dichloromethane (50ml x 3), dehydrated with Na2SO4, and then concentrated to obtain a yellow oily substance. This oily substance was purified using a silica gel column to obtain 2.9 g of compound 8.
[0136] (vi) Synthesis of B-423 To a solution of compound 8 (2.9 g, 4.8 mmol) in dichloromethane (20 ml), HCl / EtOAc (4 M, 50 ml) was added at 0° C. and stirred at 30° C. for 2 hours to obtain a pale yellow solution. The solvent was removed under reduced pressure, and then dichloromethane (50 ml) was added. The mixture was washed with saturated aqueous NaHCO3 solution (100 ml) to obtain 2.5 g of B-423. The NMR assignment values of the obtained ligand B-423 are shown below. [NMR] 1 H NMR (CDCl3, δ, ppm): 7.49 (t, 1H), 7.33 (t, 1H), 7.22 (m, 4H), 6.93 (d, 1H), 6.81 (t, 1H), 6.49(dd, 4H), 6.46(br, 1H), 3.56(s, 12H), 2.63(sept, 2H), 1.05(d, 6H), 1.04(d, 6H); 31 P NMR(CDCl3, δ, ppm):-61.6(s).
[0137] 2) Synthesis of B-423 / Ni complex The B-423 / Ni complex was synthesized using the B-423 ligand and bisacetylacetonate nickel(II) (referred to as Ni(acac)2) in a 1:1 reaction between B-423 and Ni(acac)2, in accordance with Example 1 of WO 2010 / 050256.
[0138] <(Production Examples 1 and 2): Production of Ionomer-Based Resin Precursor> Using a transition metal complex (B-423 / Ni complex or B-27DM / Ni complex), ethylene / tBu acrylate / acrylic acid ester copolymer and ethylene / tBu acrylate / norbornene copolymer were produced. The copolymers were produced with reference to Production Example 1 or Production Example 3 described in JP 2016-79408 A, and the production conditions such as metal catalyst type, metal catalyst amount, trioctyl aluminum (TNOA) amount, toluene amount, comonomer type, comonomer concentration, ethylene partial pressure, polymerization temperature and polymerization time, as well as the production results, are shown in Table 1, and the physical properties of the obtained copolymers are shown in Table 2. However, "not detected" in the table means below the detection limit.
[0139] [Table 1]
[0140] [Table 2]
[0141] <(Resin 1 and Resin 2): Production of Ionomer-Based Resins> In a 500 ml separable flask, 40 g of the copolymer of Production Example 1 or Production Example 2, 0.8 g of paratoluenesulfonic acid monohydrate, and 185 ml of toluene were added and stirred at 105° C. for 4 hours. 185 ml of ion-exchanged water was added, stirred, allowed to stand, and then the aqueous layer was extracted. Thereafter, the addition and withdrawal of ion-exchanged water was repeated until the pH of the extracted aqueous layer reached 5 or more. The solvent was distilled off under reduced pressure from the remaining solution, and the solution was dried until it reached a constant weight. In the IR spectrum of the obtained resin, the 850 cm -1 The disappearance of the peak near 1730 cm -1 The decrease in the peak near 1700 cm originates from the carbonyl group of the carboxylic acid (dimer). -1 An increase in the peak near As a result, decomposition of t-Bu ester and generation of carboxylic acid were confirmed, and ionomer base resin 1 and resin 2 were obtained. The physical properties of the obtained resins are shown in Table 3. In the following table, "E", "AA", "iBA", and "NB" are abbreviations for "ethylene", "acrylic acid", "isobutyl acrylate", and "norbornene" as structural units contained in the base resin, respectively. However, "not detected" in the table means below the detection limit.
[0142] [Table 3]
[0143] Examples 1 to 3 Ionomer Production 1) Preparation of Na ion source A Na ion source was prepared by adding 22 g of ethylene / methacrylic acid (MAA) copolymer (Mitsui Dow Polychemicals, brand: Nucrel N1050H) and 18 g of sodium carbonate to a Labo Plastomill (Roller Mixer R60) manufactured by Toyo Seiki Co., Ltd., equipped with a small mixer with a capacity of 60 ml, and kneading the mixture at 180°C and 40 rpm for 3 minutes.
[0144] 2) Preparation of Zn ion source A Zn ion source was prepared by adding 21.8 g of ethylene / methacrylic acid (MAA) copolymer (Mitsui Dow Polychemicals, brand: Nucrel N1050H) to a Toyo Seiki Co., Ltd. Labo Plastomill: Roller Mixer R60 equipped with a 60 ml small mixer, 18 g of zinc oxide, and 0.2 g of zinc stearate, and kneading at 180 °C and 40 rpm for 3 minutes.
[0145] 3) Preparation of ionomer Using the base resin and Zn ion source shown in Table 4, the ionomers of Examples 1 to 3 were prepared as follows so as to have the degrees of neutralization shown in Table 4. 40 g of the base resin was added to a Toyo Seiki Co., Ltd. Labo Plastomill: Roller Mixer R60 equipped with a 60 ml small mixer, and dissolved by kneading for 3 minutes at 160°C and 40 rpm. Then, a Zn ion source was added so as to achieve the desired degree of neutralization, and kneading was continued for 5 minutes at 250°C and 40 rpm. In the IR spectrum of the obtained resin, the 1700 cm -1 The peak at 1560 cm originating from the carbonyl group of the carboxylate group decreased. -1 The peak around 1700 cm originating from the carbonyl group of the carboxylic acid (dimer) increased. -1 From the decrease in the peak near the peak, it was confirmed that an ionomer with the desired degree of neutralization had been produced. The physical properties of the obtained ionomer are shown in Tables 4 and 5.
[0146] Comparative Example 1: E / MAA-Based Dual Ionomer An ionomer resin (manufactured by Dow Mitsui Polychemicals Co., Ltd., brand: HIMILAN HIM1555), which is a copolymer of ethylene, methacrylic acid, and sodium methacrylate and was produced by a high-pressure radical process, was used as the ionomer in Comparative Example 1. The physical properties are shown in Tables 4 and 5. In addition, the values of the degree of neutralization in Tables 4 and 5 are actual values measured by the method described in the specification.
[0147] Comparative Example 2: E / MAA-Based Dual Ionomer An ionomer resin (manufactured by Dow Mitsui Polychemicals Co., Ltd., brand: HIMILAN HIM1652), which is a copolymer of ethylene, methacrylic acid, and zinc methacrylate and was produced by a high-pressure radical process, was used as the ionomer in Comparative Example 2. The physical properties are shown in Tables 4 and 5. In addition, the values of the degree of neutralization in Tables 4 and 5 are actual values measured by the method described in the specification.
[0148] [Table 4]
[0149] [Table 5]
[0150] <Consideration of the results of the Examples and Comparative Examples> From the results shown in Table 5, comparing Examples 1 to 3 with Comparative Examples 1 and 2, the ethylene-based ionomer according to the present invention has a better balance of flexibility, elastic recovery, impact resistance, and abrasion resistance than the ethylene-based ionomers of the comparative examples which do not satisfy the specific requirements according to the present invention. As shown in Examples 1 to 3, the ethylene-based ionomer of the present invention has a good balance of flexibility, elastic recovery, impact resistance and abrasion resistance, and is confirmed to be suitable for gaskets. [Industrial Applicability]
[0151] According to the present invention, it is possible to provide an ethylene-based ionomer gasket that is suitable for bottle cap closure liners and sealing parts for electronic devices. That is, the gasket containing the ethylene-based ionomer of the present invention has an excellent balance of flexibility, elastic recovery, impact resistance and abrasion resistance, and is therefore highly useful industrially.< / e> < / e> < / e> < / e>
Claims
1. An ethylene-based ionomer for gaskets satisfying the following (a) to (f): (a) A copolymer (P) comprising, as essential constituent units, a structural unit (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) which is a noncyclic monomer which is a (meth)acrylic acid ester or a cyclic monomer which is a norbornene-based olefin other than the structural units (A) and (B), and in which the structural unit amount of the structural unit (B) is 2 to 20 mol %, at least a part of the carboxyl group and / or the dicarboxylic anhydride group is converted to a metal-containing carboxylate containing at least one kind of metal ion selected from Group 1, Group 2, or Group 12 of the periodic table, and having a complex modulus G measured with a rotational rheometer * The phase angle δ at the absolute value of 0.1 MPa is 50 to 75 degrees. (b) The melt flow rate (MFR) at a temperature of 190° C. and a load of 2.16 kg is 0.1 to 30 g / 10 min. (c) The elastic recovery rate in a tensile test is 65 to 100%. (d) The tensile modulus is 20 to 104 MPa. (e) Tensile impact strength of 700 KJ / m 2 That's all. (f) The amount of wear in an abrasion test is less than 10 mg.
2. The copolymer (P) 13 2. The ethylene-based ionomer for gaskets according to claim 1, wherein the number of methyl branches calculated by C-NMR is 50 or less per 1,000 carbon atoms.
3. The copolymer (P) 13 2. The ethylene-based ionomer for gaskets according to claim 1, wherein the number of methyl branches calculated by C-NMR is 5 or less per 1,000 carbon atoms.
4. The ethylene-based ionomer for gaskets according to any one of claims 1 to 3, wherein the structural unit (A) is a structural unit derived from ethylene.
5. The ethylene-based ionomer for gaskets according to any one of claims 1 to 4, wherein the copolymer (P) is produced using a transition metal catalyst containing a transition metal of Groups 8 to 11 of the periodic table.
6. 6. The ethylene-based ionomer for gaskets according to claim 5, wherein the transition metal catalyst is a metal complex comprising a ligand selected from phosphorus sulfonic acid or phosphorus phenol and a transition metal selected from nickel or palladium.
7. A gasket comprising the ethylene-based ionomer according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ionomer resin and manufacture thereof
JP1988270709A
Cap liners, closures and gaskets from multi-block polymers
JP2008545017A
ionomer film or sheet and solar cell modules containing the same
JP2011507278A
Solar cell module comprising low haze encapsulant
JP2015195394A
Method for producing ethylenic ionomer, and the ethylenic ionomer
JP2016079408A